Court-Approved Electroconvulsive Therapy in Patients Unable to Provide Their Own Consent: A Case Series. Issue 3 (September 2015) - Dare, Folabo Y.; Rasmussen, Keith G.
Abstract : Abstract: For patients who lack capacity to consent to electroconvulsive therapy (ECT) for various reasons (intellectual disability, severe mental illness, dementia, etc), court approval must be obtained to proceed with the treatments. We reviewed our experiences on a busy tertiary center ECT service in which we have treated 24 patients in recent years under the auspices of court approval for consent. We found that these patients generally tolerated the treatments well and had noticeable improvement in their symptoms as well as overall better quality of life. In particular, although the patients were unable to provide their own consent for ECT, they were amenable to receive the treatments and did not seem resistant or hostile to the treatment process. We conclude that, in patients unable to provide their own consent, court-approved ECT is well tolerated.